An Alternative to the Arbuzov Reaction: Generation and Transformation of α-Dialkyl-Substituted Methylphosphonate Carbanions via an SET Reduction Process - Zhang, Li; Shi, Jianxun; Fang, Yewen (Synthesis, 2022)
With B-alkyl Suzuki cross-coupling as the strategy, 1-alkyl-substituted ethenylphosphonates could be efficiently accessed via palladium-catalyzed reactions of α-phosphonovinyl tosylates with B-alkyl-9-borabicyclo[3.3.1]nonane (B-alkyl-9-BBN). Using the α-alkylethenylphosphonates as radical acceptors, visible-light-driven photocatalytic Giese-type and cyclopropanation reactions based on reductive radical-polar crossover have been successfully developed. The redox-neutral photocatalysis serves as a viable strategy for the preparation of various 1,1-dialkyl-substituted methylphosphonates and 1-alkylcyclopropylphosphonates.
Keywords: Suzuki reaction; redox-neutral photocatalysis; single-electron transfer; SET reduction; 1,1-dialkylmethylphosphonates; 1-alkylcyclopropylphosphonates